Dust Aerosol’s Deposition and its Effects on Chlorophyll-A Concentrations Based on Multi-Sensor Satellite Observations and Model Simulations: A Case Study - Wang, Wencai; He, Zhizheng; Hai, Shangfei; Sheng, Lifang; Han, Yongqing; Zhou, Yang (Frontiers in Environmental Science, 2022)
Asian dust deposition is one of the natural pathways to provide nutrients to the Pacific Ocean, when dust aerosol deposited to the ocean, it will affecting the biological productivity and hence climate. In this paper, we analyzed a dust process that occurred in Taklimakan Desert during 21-25 May, 2019 by employing multi-sensor satellite observations and WRF-Chem model. It is found that dust aerosols rise in the Taklimakan Desert, moving eastward at high altitudes under the effect of the strong mid-latitude westerly winds, passing over the downwind regions, and deposition in the Pacific Ocean. Dust deposition result in the rapid increase of chlorophyll-a (Chl-a) concentration and particulate organic carbon (POC) after two days, Chl-a concentration is 175% higher than the average value over 5-year period, POC shows the similar trend as the Chl-a concentration which increase 873%.